AutoCAD 2D: step by step graphical guide - Latip, Ramlan; Azahar, Arman Hadi; Harun, Mohamad Haniff (Penerbit UTeM Press, 2024)
This book is a guide on how to use AutoCAD software. It is suitable for young engineers and students from technical schools. The reader will be introduced to AutoCAD software step by step. It provides guidance using simple terms and comes in 9 chapters.